Prevalence and predictors of problem gambling among Swedish male elite football players: a cross-sectional study - Johanna Gripenberg; Tobias H Elgán; Håkan Wall (BMJ Open Sport & Exercise Medicine)
Objectives This study aimed to assess the prevalence of problem gambling and gambling behaviours among Swedish elite male football players and explore their awareness of gambling-related policies within their clubs. A secondary objective was to identify factors associated with problem gambling in this group.Methods A cross-sectional survey was conducted in 2021 among players from the 32 clubs in Sweden’s top two football leagues (Allsvenskan and Superettan). Data were collected through an online survey utilising the Problem Gambling Severity Index (PGSI) alongside additional questions on gambling types, mental health, alcohol use, match-fixing and policy awareness. Multivariable logistic regression was employed to analyse predictors of problem gambling.Results A total of 416 footballers participated, yielding a response rate of 58%. The prevalence of gambling in the past year and problem gambling (PGSI score≥3) was 60.6% and 6.6%, respectively. While 72% of past-year gamblers reported engaging in sports betting, only slots (OR=7.46, p=0.01) and bingo (OR=6.08, p=0.02) were significant predictors of problem gambling. Only 32% of respondents were aware of a gambling policy within their clubs. Additionally, 17.8% reported depressive symptoms, while 13.9% experienced anxiety.Conclusions This study highlights the high prevalence of problem gambling among elite Swedish footballers, with slots and bingo posing higher risks. Sports betting, while prevalent, may contribute to the gamblification of football. The role of gambling sponsorships in normalising gambling among footballers requires further investigation. There is a need for longitudinal studies on gambling behaviours and policy awareness within clubs, and comprehensive preventive strategies to address gambling-related harm among footballers.